The Analysis of Adjunct to Refusal Expressions in a Refusal Discourse: A Contrastive Study between Japanese Native Speakers and Indonesian Japanese Learners - Hayati, Novia (Universitas Negeri Semarang, 2024)
The study reports on the analysis of Adjunct to Refusal Expressions used by Japanese Native Speaker (JNS) and Indonesian Japanese Learners (IJL) in a refusal discourse. The aims are to see whether both use Adjunct to Refusal Expressions in a refusal interaction and to observe what type of expressions they use when refusing in the interaction, investigating the similarities and differences in their use from the first refusal stage to the stage where the intent of refusal is accepted by the refusee. The mixed method research involved 60 participants consisting of 30 pairs JNS female university students and 30 pairs of IJL female university students. The male students were not involved in this study due to the lack numbers of those learning Japanese language in the university. IJL students represented beginner and intermediate levels (N5, N4, and N3). The data were collected by situating the participants in a role play based on the setting given while being videotaped. The setting is a refusal to a close friend’s request. The data were analyzed by using a semantic formula framework, focusing on Adjunct to Refusal expressions modified from Beebe et al (1990), Yoshida (2015) and Hayati (2020, 2023). The results showed that both JNS and IJL employed Adjunct to Refusal expressions in their refusal discourse. There was no significant difference in the use of Adjunct to Refusal by JNS and IJL with χ2(1) = 1.270, p = .2597. However, JNS used higher Adjunct to Refusal expressions (46,7%) than IJL (33,3%). Further, their preferences in using certain type of Adjunct to Refusal expressions were similar in that they highly used information request type, whereas the differences could be seen from the absent use of confusion as Adjunct to refusal in JNS and that of backchannel response in IJL.